Methods of Retinal Ganglion Cell Differentiation From Pluripotent Stem Cells - Gill, Katherine P. (Transl Vis Sci Technol, 2014)
Glaucoma, the worldwide leading cause of irreversible blindness, is characterized by progressive degeneration of the optic nerve and loss of retinal ganglion cells. Research into glaucoma pathogenesis has been hampered by difficulties in isolating and culturing retinal ganglion cells in vitro. However, recent improvements in laboratory techniques have enabled the generation of a variety of mature cell types from pluripotent stem cells, including retinal ganglion cells. Indeed, stem cell-based approaches have the potential to revolutionize the field by providing an unlimited source of cells for replacement therapies and by enabling development of in vitro disease models for drug screening and research. Consequently, research aimed at directing pluripotent stem cells to differentiate into retinal ganglion cells has expanded dramatically during the past decade, resulting in significant advances in technique and efficiency. In this paper, we review the methodology for retinal ganglion cell differentiation from pluripotent stem cells of both mouse and human origin and summarize how these techniques have opened up new avenues for modelling glaucoma. Generation of stem cell–derived retinal ganglion cells will have significant translational values, providing an in vitro platform to study the mechanisms responsible for pathogenesis and for drug screening to improve treatment options, as well as for the development of cell therapies for optic neuropathies such as glaucoma.